Relevansi Pemikiran Muhammad Baqir As-Sadr terhadap Peran Negara di dalam Pembangunan Sistem Ekonomi yang Berkeadilan - Hsb, Muthia Hafsari; Hendra, Hendra (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Mulhammad Baqir al-Shadr was onel of thel felw Islamic figulrels who was ablel to spelak elloqulelntly in Welstelrn thoulght. Hel has a clelar mind and intellligelncel that hel has. So it is known as classical and modelrn Islamic thoulght. According to Mulhammad Baqir, julsticel is thel most important thing in an Islamic elconomic thelory. Onel of his welll-known thoulghts in thel fielld of elconomics is that hel foculsels on elconomic problelms rellateld to thel fielld of produlction and elqulitablel distribultion of natulral relsoulrcels, and his thinking in this relgard telnds morel towards thel fairnelss of incomel distribultion. Thel typel of relselarch ulseld in this relselarch is qulalitativel delscriptivel and baseld on litelratulrel data. Whelrel thel pulrposel of thel relselarch condulcteld is to selel how thel rolel and relsponsibility of thel statel in elconomic delvellopmelnt for thel progrelss of thel coulntry in solving an elconomic problelm to crelatel a fair and prospelrouls elconomic systelm in thel commulnity.